TATALAKSANA PROMOSI KESEHATAN IBU DAN ANAK DIPUSKESMAS SIMPANG TIGA PEKANBARU - Winda Septiani (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
The Human Development Index (HDI) is a composite indicator that shows the quality of humans comprehensively in terms of economy, education and health. From the data obtained at the Simpang Tiga Puskesmas, that based on the data obtained in the last 3 years the coverage of the MCH program has increased every year. For this reason, a study was conducted on how to carry out MCH promotion in Puskesmas in managing health services in a good management function in terms of: 1) empowerment, 2) atmosphere development, 3) advocacy and 4) partnership. This study aims to determine the description of the management of MCH promotion in the Simpang Tiga Puskesmas, Pekanbaru City. The research design used is descriptive qualitative research, which is carried out through in-depth interviews. Determination of informants using purposive sampling technique. There were 4 informants consisting of 2 informants from KIA officers and the Head of Administration and 2 other informants, namely the head of the puskesmas and the service recipient (community). The results of the research are: 1) health promotion strategies through community empowerment are carried out in stages by health workers at Simpang Tiga Public Health Center and community empowerment cadres (KPM) to individuals, groups and communities in the form of counseling, counseling, demonstrations and dialogues; 2) Efforts to maintain an atmosphere through health promotion activities outside the building and inside the building, by using promotional media and the behavior of health workers; 3) advocacy is aimed at and involves commitment and support such as Sub-District Leaders in the work area of ​​Simpang Tiga Public Health Center and Pekanbaru City Health Office in making policies / regulations and procuring resources; and 4) the current partnership still relies on the presence of partners who offer certain activities to participate in health promotion activities. Keywords: Management, health promotion program, KIA